2015
DOI: 10.1002/ajmg.a.37519
|View full text |Cite
|
Sign up to set email alerts
|

Genotype–phenotype characterization in 13 individuals with chromosome Xp11.22 duplications

Abstract: We report 13 new individuals with duplications in Xp11.22-p11.23. The index family has one male and two female members in three generations with mild-severe intellectual disability (ID), speech delay, dysmorphic features, early puberty, constipation, and/or hand and foot abnormalities. Affected individuals were found to have two small duplications in Xp11.22 at nucleotide position (hg19) 50,112,063-50,456,458 bp (distal) and 53,160,114-53,713,154 bp (proximal). Collectively, these two regions include 14 RefSeq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Importantly, this study also performed qPCR and showed that HUWE1 expression levels were elevated in these patient samples, consistent with an overexpression/gain-of-function effect on HUWE1. Subsequent studies that used exome or next generation sequencing identified HUWE1 CNVs in numerous other families with non-syndromic ID [66][67][68][69][70][71][72][73][74][75] (Table 1).…”
Section: Huwe1 Copy Number Variations and Nonsyndromic Intellectual Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, this study also performed qPCR and showed that HUWE1 expression levels were elevated in these patient samples, consistent with an overexpression/gain-of-function effect on HUWE1. Subsequent studies that used exome or next generation sequencing identified HUWE1 CNVs in numerous other families with non-syndromic ID [66][67][68][69][70][71][72][73][74][75] (Table 1).…”
Section: Huwe1 Copy Number Variations and Nonsyndromic Intellectual Dmentioning
confidence: 99%
“…The most compelling links are to epilepsy or seizure [64,67,[69][70][71][72][73][74]. Autism-like behaviors have also been documented [66,70,72]. While seizure/epilepsy and autism are observed in some individuals with HUWE1 CNVs, the genetic links between HUWE1 and these neurodevelopmental conditions are much less clear and less consistent than ID.…”
Section: Huwe1 Copy Number Variations and Nonsyndromic Intellectual Dmentioning
confidence: 99%
“…They also reported a 1-year-old boy with a 61-kb duplication at Xp11.23 with global developmental delays, including motor, verbal, and poor feeding. 13 The female presented here had a very small duplication of 175 kb yet had severe ID.…”
Section: Discussionmentioning
confidence: 79%
“…nonsyndromic ID. To date, 18 unrelated families with overlapping duplications at Xp11.22 have been described, and most patients share similar clinical features, including ID, delayed motor development and delayed language [6][7][8][9][10]. Comparing these duplicated segments, the HUWE1 gene, coding the E3 ubiquitin protein ligase, turned out to be duplicated in all previously described patients.…”
mentioning
confidence: 99%
“…Comparing these duplicated segments, the HUWE1 gene, coding the E3 ubiquitin protein ligase, turned out to be duplicated in all previously described patients. Therefore, an increased dosage of HUWE1 is believed to be responsible for nonsyndromic ID [6][7][8][9][10]. To date, little is known about the clinical consequences of other genes involved in this interval, and the genotype-phenotype relationship is still limited.…”
mentioning
confidence: 99%